Optimalisasi Penerapan Aplikasi Inapornet untuk Pemberitahuan Melakukan Kegiatan Usaha di KSOP Kelas 1 Tanjung Balai Karimun: Penelitian - Meriah Kita Deliani; Shinta Aulia Hidayah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
In order to modernize ports through digital transformation, the Indonesian government introduced Inapornet as an integrated electronic port service system to simplify maritime sector operations and document management. Inapornet functions as a centralized platform that accelerates information exchange, customs procedures, and increases transparency in shipping services. This study aims to analyze the implementation and optimization of Inapornet at the Class I Port Authority (KSOP) of Tanjung Balai Karimun using a qualitative descriptive approach and logistic regression analysis during February–August 2025, involving all shipping and logistics companies under the KSOP's supervision. The results showed that the main obstacles were limited digital skills of officers (65%), internet instability (66%), complexity of ship documents (62%), and large file sizes (62%), which hampered the system's effectiveness. Therefore, the study recommends regular training, periodic system evaluations, and improvements in infrastructure and digital literacy. Optimizing Inapornet is expected to improve service quality, operational efficiency, and support the realization of a smart, efficient, and transparent port.